Diffusion and Adoption of Destana in Tropical Disaster-Prone Socio-Ecological Systems - Rosdiana, Zulfa; Taqiuddin, Moh.; Hadi, Agus Purbathin (Jurnal Biologi Tropis, 2026)
Tropical island villages face complex disaster risks due to the interaction between geophysical hazards, hydrometeorological threats, social vulnerability, and local institutional capacity. This study aimed to analyze the diffusion and adoption of the Disaster Resilient Village Program (Desa Tangguh Bencana, Destana) in strengthening community preparedness in Sambelia District, East Lombok, Indonesia. A qualitative multi-site case study was conducted in Sugian, Belanting, and Obel-Obel villages from November to December 2025. Data were collected through semi-structured interviews, observation, and document review involving 17 informants from the regional disaster management agency, village governments, disaster volunteers, NGO/TSBD actors, community leaders, and residents. Data were analyzed thematically using Rogers’ diffusion of innovations framework and a disaster risk perspective linking hazards, vulnerability, and capacity. The results show that Destana is relevant for multi-hazard villages, but its adoption remains partial. Administrative recognition was not fully followed by strong village documentation, active local institutions, continuous communication, or integration into village development planning. Community members accepted disaster preparedness practices, yet they did not always recognize Destana as a formal village-based innovation. The study concludes that Destana needs stronger risk communication, institutional renewal, regular simulation, and integration into village planning to transform administrative designation into sustained socio-ecological resilience.